A field study of the individual and combined effect of ventilation rate and lighting conditions on pupils' performance. (15th March 2020) - Hviid, Christian A.; Pedersen, Christian; Dabelsteen, Kent Helmann
Abstract: A field lab study was conducted to determine how much the indoor climate parameters, ventilation and lighting, influence children's academic abilities. The study involved 92 children, aged 10–12 years, who over four weeks answered a questionnaire and three different performance tests, which measured their processing speed, concentration, logical reasoning and math solving abilities. An experimental design was constructed to test the effect of changing the lighting from constant warm light with a maintained correlated colour temperature average of 2900 K and lighting level of 450 lux to a dynamic cool light of 4900 K and 750 lux. The change was tested at both low (3.9 l/s per person) and high ventilation rate (10.6 l/s per person). The results showed that processing speed (6.6%, P < 0.001), concentration (8.3%, P < 0.001) and math skills (11.8%, P < 0.006), improved the most in the combined scenario with high ventilation rate and dynamic cool lighting. The logical reasoning test did not show any significant changes. The questionnaire results of the pupils' perception of the indoor environment suggested that they were satisfied in general, but the indoor environmental changes had only very limited effect on how they perceived the classroom. The combination of dynamic lighting and increased ventilation rate indicated a boosted positive impact on the speed and concentration of the children which means that future renovations would benefit from a holistic design including both of these factors. Highlights: Schoolchildren's performance is affected by ventilation rate and lighting conditions. The effect of individual measures was small compared to combined effect. Neither improved ventilation rate, nor lighting conditions should be individual measures. Combine improved ventilation rate and lighting conditions to boost performance. The results support a holistic view on indoor environmental refurbishment.